7 Implantable cardiac device generator change pathways: an opportunity for optimising device prescription. (5th June 2017) - Bolam, Helena; Thompson, Daniel; Waller, James; Andrews, Neil; Kirubakaran, Senthil; Kalra, Paul; Morton, Geraint
Abstract : Introduction: Implantation of cardiac devices including permanent pacemakers (PPM), cardiac resynchronisation therapy with defibrillators (CRT-D) or without (CRT-P) is increasingly common. Follow up, including arranging generator change, is frequently carried out by cardiac physiologists, with minimal physician input. Many patients clinical status will change during the lifetime of the device. Generator change is an opportunity to review the original device prescription. We report the impact of introducing routine screening prior to generator change into an established comprehensive device programme. Methods: Two pathways were implemented. Patients with a PPM due generator change were screened by cardiac physiologists using a proforma assessing symptoms, QRS duration and right ventricular (RV) pacing burden. Those with heart failure symptoms, in particular breathlessness, and a prolonged native QRS or >40% RV pacing had an echocardiogram and multidisciplinary team (MDT) discussion within 2 weeks. If device upgrade was potentially indicated the patient was reviewed in clinic prior to generator change. The goal was to discuss all patients with an ICD/CRT-D due generator change at MDT. Those with changes in clinical status that may affect the appropriateness of ongoing defibrillator therapy were reviewed in clinic. Results: The first 11 months, October 2015 to August 2016, following implementation of these pathways were studied. 189 consecutive patients (145 PPM, 20 CRT-P and 24 CRT-D/ICD), mean age of 77, were included. The pathways resulted in a change in the type of device therapy in 8 patients; 6/145 (4%) of those due PPM and 2/24 (8%) due CRT-D/ICD generator change (table 1). 145 (100%) of PPM patients were proforma screened. 139/145 PPM patients (96%) went on to have PPM generator change. 17 (12%), identified as potential candidates for upgrade to CRT, had echocardiography. 5 (3%) of these had severe LV impairment and underwent physician and MDT review. 4 patients (3%) were ultimately upgraded to CRT devices. CRT was not appropriate in 1 patient. In 2 (1%) patients ongoing device therapy of any kind was felt to be inappropriate (1 potential upgrade and 1 PPM box change) and no procedure was undertaken. 10/24 (42%) patients due a CRT-D/ICD generator change were reviewed at MDT. Of these 2 (20% of those reviewed) went on to have their devices downgraded from CRT-D to CRT-P after informed discussion. Conclusions: Physiologist-led device follow up can be effectively extended to include robust screening of patients to ensure they get the most appropriate device at the time of generator change. Excellent rates of PPM screening were achieved whereas ICD screening needs to be improved. Relatively few patients had their destination device changed as a result of these pathways. However there is significant morbidity associated with receiving inappropriate device therapy, justifying implementation of a simple screening process to improve care.